Breast Cancer Screening in Europe - Gad, Adel; Turco, Marco Rosselli Del (ESO Monographs, European School of Oncology, 1993)
As controlled trials have demonstrated that in many European countries breast cancer mortality may be reduced by population-based mammographic screening of women over the age of 50, there is mounting pressure to introduce new service screening programmes. How should these programmes be planned and monitored ? Is it cost-effective ? We invited experts whowork with the principal screening programmes in Europe to answer these questions and to describe their experiences. Particualr attention has been given to planning, organisation and monitoring new screening programmes in order to achieve optimal results